Etnografiando “Juegos recreativos y tradicionales de la calle” en el municipio de Caldas (Colombia). Un desafío metodológico en investigación curricular (2012)
ABSTRACT: This text presents an appropriation of the methodology that a group of researchers used for conducting the ethnography of a Best Practice referenced in educational processes of the body in Colombia under the international project called “Documents, systematization and interpretation of best teaching practices in the education process of the body in school”. The choice of this research approach, the search for a generalizing practice, the definition of the research object, the levels of analysis and triangulation, and the configuration of a narrative ethnographic made up a story level, in order to inform the learning processes, the reflections and regularities resulting from the actual conduct of research. The resulting product provides, as referenced experience, considerable contextualizing elements in the field of school ethnography.